In-situ encapsulation of α-Fe2O3 nanoparticles into ZnFe2O4 micro-sized capsules as high-performance lithium-ion battery anodes. (10th June 2021) - Wu, Wei; Wei, Yongshan; Chen, Hongjiang; Wei, Keyan; Li, Zhitong; He, Jianhui; Deng, Libo; Yao, Lei; Yang, Haitao
Graphical abstract: Highlights: In-situ encapsulating α-Fe2 O3 NPs into ZnFe2 O4 capsules by facile co-precipitation. ZnFe2 O4 scaffold suppresses α-Fe2 O3 ' grain growth and offers a porous nature. Interconnected pores and enhanced interfacial conductivity facilitate Li + mobility. Exceptional long-term cycling and rate capability were demonstrated. Abstract: Transition metal oxides as anode materials for high-performance lithium-ion batteries suffer from severe capacity decay, originating primarily from particle pulverization upon volume expansion/shrinkage and the intrinsically sluggish electron/ion transport. Herein, in-situ encapsulation of α-Fe2 O3 nanoparticles into micro-sized ZnFe2 O4 capsules is facilely fulfilled through a co-precipitation process and followed by heat-treatment at optimal calcination temperature. The porous ZnFe2 O4 scaffold affords a synergistic confinement effect to suppress the grain growth of α-Fe2 O3 nanocrystals during the calcination process and to accommodate the stress generated by volume expansion during the charge/discharge process, leading to an enhanced interfacial conductivity and inhibit electrode pulverization and mechanical failure in the active material. With these merits, the prepared α-Fe2 O3 /ZnFe2 O4 composite delivers prolonged cycling stability and improved rate capability with a higher specific capacity than sole α-Fe2 O3 and ZnFe2 O4 . The discharge capacity is retained at 700 mAh g −1 after 500 cycles at 200 mA g −1 and 940 mAh g −1 after 50 cycles at 100 mA g −1 . This work provides a new perspective in designing transition metal oxides for advanced lithium-ion batteries with superior electrochemical properties.